2010 5th ESA Workshop on Satellite Navigation Technologies and European Workshop on GNSS Signals and Signal Processing (NAVITEC 2010
DOI: 10.1109/navitec.2010.5708053
|View full text |Cite
|
Sign up to set email alerts
|

ENCORE: Enhanced code Galileo receiver for land management applications in Brazil

Abstract: Taking benefit of the new Galileo ranging signals, the ENCORE (Enhanced Code Galileo Receiver) project aims to develop a low-cost Land Management Application to cover needs of the Brazilian market in terms of geo-referencing and rural/urban cadastre, using a low-cost Enhanced Galileo Code Receiver as baseline. Land management applications require precision and accuracy levels from a few to several decimetres that are under-met with current pseudorange-based receiver and over-met with phase observations. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Based on the results presented above and on the Galileo E1 signal characteristics (CBOC(6,1,1/11) modulation), it was expected that Galileo performances, in terms of code measurements noise, would outperform the ones for GPS L1 C/A by a factor of at least 3, as confirmed in other studies as the ENCORE project (Silva, P, et al, 2011), where measurement noise as low as 13cm has been reported. …”
Section: Code Tracking Performancesupporting
confidence: 66%
“…Based on the results presented above and on the Galileo E1 signal characteristics (CBOC(6,1,1/11) modulation), it was expected that Galileo performances, in terms of code measurements noise, would outperform the ones for GPS L1 C/A by a factor of at least 3, as confirmed in other studies as the ENCORE project (Silva, P, et al, 2011), where measurement noise as low as 13cm has been reported. …”
Section: Code Tracking Performancesupporting
confidence: 66%